Evidence for a seasonally dependent ring plasma in the region between Saturn's A Ring and Enceladus' orbit. Issue 8 (17th August 2015) - Persoon, A. M.; Gurnett, D. A.; Kurth, W. S.; Groene, J. B.; Faden, J. B.
Abstract: Equatorial electron density measurements from the Cassini Radio and Plasma Wave Science experiment are derived from the upper hybrid resonance frequency from Saturn Orbit Insertion (SOI) on 1 July 2004 through 21 May 2013. These densities are used to determine the characteristics of the plasma in the inner magnetosphere of Saturn between the outer edge of the A Ring and the orbit of Enceladus. Electron densities obtained when Cassini first arrived at Saturn on 1 July 2004 showed a plasma distribution decreasing radially outward from Saturn in the direction of Enceladus, the expected distribution of a centrifugally driven plasma expanding radially outward from a source in the main rings. We examine equatorial electron densities in the region between 2.4 and 4.0 Rs and show that the density measurements in this region exhibit a strong seasonal dependence resulting from photon‐induced decomposition of icy particles on the ring surfaces, a decomposition process which is controlled by the solar incidence angle. This seasonal dependence will have plasma density implications for Cassini when the spacecraft returns to the region just beyond the A Ring in 2016. Key Points: Observe seasonal variation in equatorial electron densities inside 3.25 Rs Seasonal variation diminishes with distance from Saturn, vanishing beyond 4.0 Rs Observe evidence for propagation of ring plasma near inner edge of E Ring